Penerapan Green Banking Pada Perbankan BUMN di Indonesia: Studi Kasus pada Perbankan BUMN yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2022 - Devi Nur Alfiah; Lilik Pujiati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The implementation of green banking is an effort to change the old paradigm of national development from a greedy economy to a green economy where the greedy economy is seen from the value of the gross domestic product which results in the exploitation of natural resources, while the green economy is economic growth that still pays attention to the 3Ps (people, profit and planets). The 3P concept is a sustainable development effort. Method: The research approach used is descriptive qualitative. According to Moleong (2005:6), qualitative research is research that intends to understand phenomena about what is experienced by research subjects, for example behavior, perceptions, motivations, actions, etc. holistically, and by means of descriptions in the form of words and language, on a special natural context and by utilizing various natural methods. Results: The research results show that the majority of state-owned banks in Indonesia have started steps towards implementing green banking. They have issued internal policies that support carbon emission reduction practices, such as the use of renewable energy and energy efficiency. Conclusion: the implementation of green banking in state-owned banking in Indonesia has progressed in the 2021-2022 period. Most state-owned banks have adopted practices of reducing carbon emissions, sustainable project financing, and developing environmentally friendly products and services. However, there are still challenges in implementing green banking, such as a lack of understanding and awareness of the benefits and business potential of this practice, as well as limited resources in implementing it widely.